A proposed library programs for the implementation of a self-circulation system in the University of the Philippines Diliman Libraries - Quindoza, Mark Lawrence R. (2012)
Circulation of library materials is one of the most vital tasks in a library. In the case of the University of the Philippines Libraries, a big percentage of the work done by the librarians includes circulation work. Since most of the unit libraries in the university are undermanned, focusing on the circulation work leads to neglecting other library duties and programs. A proposed solution for this problem was the implementation of a self-circulation system where the users could borrow the materials on their own. This was implemented in the Ateneo de Manila University Rizal Library using a commercially available system and was found to be very user-friendly and efficient.